Medical student question answering behaviour during high-stakes multiple choice examinations. (30th January 2019) - AlMahmoud, Tahra; Regmi, Dybesh; Elzubeir, Margaret; Howarth, Frank Christopher; Shaban, Sami
Evaluating student answering behaviour during high-stakes assessments may help identify deficits in students' efficiency or question answering effectiveness. We used electronic assessment logfiles to examine student answering behaviour during exams. We compared the time spent on questions based on student gender, question correctness, cognitive level and clinical discipline. Male and female students spent the same amount of time on questions however, females performed significantly better. There were significant differences in average time spent on questions answered correctly versus incorrectly and in the amount of time examinees spent on questions per cognitive level. The percentage of questions that had answers changed by examinees was 13.65% of which 5.82% changed from incorrect to correct and 2.83% changed from correct to incorrect. On average, 16.3% of questions were placed under review by examinees at some time during the exam. Students spent significantly more time on questions that were answered incorrectly and on higher cognitive level questions. Reviewing and re-answering questions was more beneficial than harmful to student marks.